DANCE STUDIOS AS AGENTS OF CULTURAL SOCIALIZATION: A SOCIOLOGICAL STUDY OF DANCE EDUCATION IN INDONESIA: DANCE STUDIOS AS AGENTS OF CULTURAL SOCIALIZATION: A SOCIOLOGICAL STUDY OF DANCE EDUCATION IN INDONESIA - Nursilah, Nursilah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study aims to analyze the role of dance studios as agents of cultural socialization in the contextof non-formal education in Indonesia. Based on the perspective of educational sociology, this studyexamines how dance studios function as spaces for the transmission of values, the formation ofartistic habitus, and cultural reproduction amidst the social dynamics of modern society. Theresearch approach used was qualitative with an ethnographic design. Data were obtained throughparticipant observation, in-depth interviews, and documentation at several traditional dance studiosin Indonesia. The analysis was conducted inductively by following the model of Miles and Huberman(1994) through the stages of data reduction, presentation, and verification. The results show thatdance studios have three main functions: (1) as non-formal educational institutions that transmitcultural and moral values; (2) as an arena for socialization that strengthens social solidarity throughcollective artistic activities; and (3) as a forum for the formation of artistic habitus and theaccumulation of cultural capital as proposed by Bourdieu (1986). The process of cultural inheritancethat takes place in the studio is generative and adaptive, enabling the reproduction of traditionalvalues in a modern context. These findings support Durkheim's (1912) view that education serves tomaintain the moral integration of society, while also broadening the understanding of arts educationas a process of socialization and cultural reproduction. This research emphasizes the importance ofstrengthening the role of studios as cultural institutions that contribute to the preservation of culturalheritage and the formation of cultural identity among the younger generation in Indonesia.